Analisis Risiko K3 Menggunakan Metode Hazard Identification Risk Assessment and Risk Control (HIRARC) Pada Pekerja di PT XYZ - Yoane Rahmanita Mulyani; Kusnadi Kusnadi; Rahman Saleh (Peneliti.net, 2022)
A work accident is an event that cannot be predicted when it occurs so that a person's activities can be disrupted in completing a job. In daily activities, potential sources of danger can be found that are easily found in the work environment, in the Production, Packing, and Maintenance section of PT. XYZ. So the purpose of this study is to analyze a potential work hazard and the level of work accidents that occur with the method used, namely the HIRARC (Hazard Identification Risk Assessment and Risk Control) method. carry out a work risk assessment or risk assessment and carry out risk control or risk control to prevent and reduce the occurrence of an accident or potential work hazard. After being analyzed according to a low risk assessment of 37%, moderate risk of 25%, high risk of 25%, and extreme risk of 13%. Furthermore, efforts to prevent work accidents using the control hierarchy are methods for eliminating, substitution, administration, engineering, and personal protective equipment (PPE) for risk control.